Biomechanical properties of a novel cervical spine implant with elastic deformation: a cadaveric study - Abudouaini, Haimiti; Wu, Tingkui; Meng, Yang; Ding, Chen; Liu, Hao; Beiyu, Wang (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Anterior cervical discectomy and fusion (ACDF) is a most frequently used surgical procedure for treating cervical radiculopathy and myelopathy. However, there is concern about the high adjacent segment degeneration (ASD) rate after ACDF surgery. We creatively designed an elastically deformable cervical implant to reduce the postoperative stress concentration. In this study, we aimed to investigate the biomechanical performance of this novel cervical implant and compare it with the commonly used cervical devices. Methods: Biomechanical test was conducted on twelve fresh-frozen human cadaveric cervical spines (C2–C7) and randomly divided into four groups according to implant types: intact group, Zero-P VA fusion (ACDF) group, the novel cervical implant group and Pretic-I artificial cervical disc (ACDR) group. An optical tracking system was used to evaluate the segmental range of motion (ROM) of the C4/C5, C5/C6, and C6/C7 segments and micro pressure sensor was used to record the maximum facet joint pressure (FJP), maximum intradiscal pressure (IDP) at the C4-5 and C6-7 segments. Results: There were no significant differences in the ROM of adjacent segments between the groups. Compared with the intact group, the ACDR group essentially retained the ROM of the operated segment. The novel cervical implant decrease some ROM of the operated segment, but it was still significantly higher than in the fusion group; The maximum FJP and IDP at the adjacent segments in the ACDF group were significantly higher than those values in the other groups, and there were no differences in the other groups. Conclusions: While the newly developed elastically deformable cervical implant does not completely maintain ROM like the artificial cervical disc, it surpasses the fusion device with regards to biomechanical attributes. After further refinement, this novel implant may be suitable for patients who are prone to severe adjacent segment degeneration after fusion surgery but no indication for artificial cervical disc surgery.